Developing Speaking Instruction Through Metacognitive Approach - Apandi, Mahdiah; Didik Santoso (PT Inovasi Pratama Internasional, 2023)
The teachers’ speaking instruction is considered successful if the student’s skills in English speaking increase. There are still many teachers who still use conventional instruction in teaching speaking. The traditional approaches to language teaching only focus on teacher-centered. This can be proved by the result of observation at MTs Al Washliyah Kolam Junior High School. Teachers should adopt approaches that can help students develop their speaking skills in a holistic way. The theoretical model of this research uses Research and Development (R & D) method by using Borg and Gall model by limiting and simplifying it to just four steps, namely, Research & Information collection, Planning, Design of Product, and Expert Judgment. The result of this research: (1) The existing speaking instruction used by the English teacher at MTs Al Washliyah Kolam Junior High School still uses the traditional method. (2) Speaking instruction is needed by the students based on the data that the highest students need the Teacher’s help (80%) to speak English, the second rank students need to conclude the lesson (73,33%) when end the learning and give an example of speaking (40%) when speaking English. (3)The model is developed by the researcher to improve students' speaking skills is considered very relevant because the model created by experts was further developed for learning English speaking. (4) The result of expert judgment, the speaking instruction model through Metacognitive approach is valid and worth testing.